2020
DOI: 10.1016/j.tifs.2020.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral potential of garlic (Allium sativum) and its organosulfur compounds: A systematic update of pre-clinical and clinical data

Abstract: Background Garlic ( Allium sativum L.) is a common herb consumed worldwide as functional food and traditional remedy for the prevention of infectious diseases since ancient time. Garlic and its active organosulfur compounds (OSCs) have been reported to alleviate a number of viral infections in pre-clinical and clinical investigations. However, so far no systematic review on its antiviral effects and the underlying molecular mechanisms exists. Scope and app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
140
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(174 citation statements)
references
References 115 publications
3
140
0
7
Order By: Relevance
“…Garlic, on the other hand, is a potent stimulant of the immune system ( Ried, 2016 ). Garlic has also strong antiviral activity and is suggested to be useful in the prevention and management of COVID-19 infection ( Rizzo et al, 2020 ; Rouf et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Garlic, on the other hand, is a potent stimulant of the immune system ( Ried, 2016 ). Garlic has also strong antiviral activity and is suggested to be useful in the prevention and management of COVID-19 infection ( Rizzo et al, 2020 ; Rouf et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Conforme descrito por Galhardi e colaboradores (2020), tal disseminação de fake news contribui para o descrédito da ciência e das instituições globais de saúde em favor do achismo. De fato, entre as principais fake news citadas pelos autores, temos em comum o uso do alho em água fervida, que até hoje não possui comprovação de eficácia no tratamento direto do coronavírus, servindo apenas como adjuvante ao estimular o sistema imunológico (KHUBBER et al, 2020;ROUF et al, 2020;SINGH;SAHU, 2020).…”
Section: Efeitos Adversos Fonteunclassified
“…Garlic is an annual bulbous herb native to Central and South Asia. The countries with the highest production are USA, China, India, Egypt, and South Korea [ 99 ]. Many studies have demonstrated that garlic has antifungal and antibacterial properties, which have been associated to the thiosulfinates and volatile sulphur compounds, which are responsible for the intense flavor of these vegetables.…”
Section: Main Raw Materials Used In Vegetable Soups and Cream Prodmentioning
confidence: 99%